Physio-chemical characterization of indigenous agricultural waste materials for the development of potting media - Kiran, Sidra; Iqbal, Javed; Danish, Subhan; Bakhsh, Allah; Bukhari, Syed Inam Ullah Shah; Bibi, Fatma; Alotaibi, Khaled D; Fahad, Shah; Nasif, Omaima; Zuan, Ali Tan Kee; Datta, Rahul (Saudi journal of biological sciences, 2021)
Organic residues are an important factor that directly affects fruiting tree seedlings' health at earlier stages. It provides a suitable environment for seedling growth by providing better nutrient ions, water, and aeration. However, low organic contents and high shrinkage of most organic materials mostly deteriorate ideal potting media characteristics. Low aeration, high water, and nutrients leaching decrease seedling growth and cause a significant loss of valuable resources. That is why the current study was conducted to screen out the best indigenous materials based on particle size to produce good characteristics bearing potting media. For that, eight different ingredients, i.e., "sugarcane", "coconut coir", "wheat straw", "rice straw", "corn cob", "leaf litter", "farmyard manure", and "sunflower heads" were collected. Initially, all the materials were air-dried and processes as per requirement. After grinding, three particles size (fine = < 2 mm, medium = 3 mm and coarse = 5 mm) were separated by sieving. Results showed that decreasing particle size in "rice straw", "corn cob", "farmyard manure," and "sunflower head" decreased leachate pH. Higher EC in leachates was negatively correlated with particle size in all potting media ingredients. Except for farmyard manure, fine particle size increases the water-holding ability of potting media ingredients. However, air-filled porosity was associated with a decrease in particle size of potting media in gradients. In conclusion, farmyard manure, "sunflower heads", "leaf litter" and "sugarcane" should be incorporated while making a combination for potting media. More investigations are suggested by mixing different particle size ingredients to prepare potting media.
Keywords: Particle size; Chemical attributes; Agricultural waste; Physical attributes; Potting media